Proinflammatory and anti-inflammatory cytokines in pregnant women chronically infected with Trypanosoma cruzi - Cardoni, Rita L. (2004)
Fil: Cardoni, Rita L. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.